Digitalizing a local language dictionary: Challenges and opportunities. - Luthfita, Winda; Yanita, Selly Rizki (Lexicography, 2023)
The National Agency for Language Development and Cultivation (henceforth, Badan Bahasa) has published many dictionaries as a government agency under the Ministry of Education and Culture of Indonesia. More than 100 dictionaries have been published since 1977. Some dictionaries have been revised by adding new entries and senses. In alignment with technological developments, Badan Bahasa has started an integration project that aims to provide an online application for their language products. In 2015, it started Program Pengayaan Kosakata (Word proposal application program), and this was followed by the launch of the online version of the Kamus Besar Bahasa Indonesia (KBBI; Comprehensive dictionary of Indonesian), Tesaurus Tematis Bahasa Indonesia (Thematic thesaurus of Indonesian), and Ensiklopedia Sastra Indonesia (Encyclopedia of Indonesian literature) in 2016. In 2020, Badan Bahasa started the development of Aplikasi Pangkalan Data Kamus, also called Aplikasi Kompilasi Kamus (AKK; Dictionary compilation application). This online application accommodates at least three kinds of dictionary - a local language dictionary, specialized dictionary, and bilingual dictionary - published by Badan Bahasa. The process has continued by developing a digitalization project targeting the digitalization of print versions of specialized dictionaries, Indonesian-local language dictionaries, and local language-Indonesian dictionaries. This article aims to discuss some challenges regarding the digitalization of dictionaries arising from the print versions, the dictionary structure, and the dictionary interface, and puts forward some solutions to deal with the issues. The research method uses qualitative methods for observing dictionary files and examining microstructure issues throughout the whole process. The results of this study are expected to support the digitalization process and dictionary development in Indonesia.